Impact of Benzo[a]Pyrene Exposure on Thyroid Gland of Individuals Workers In Oil Refining - J. Kadhim, Sara; Hussein J. Alqaisi, Alaa; Mohammed, Salam (Al-Nahrain Journal of Science, 2025)
Benzo[a]pyrene is very well known as a toxic substance. Exposure to several types of serious toxic impacts is associated with all individuals. This research determined the Benzo[a] pyrene level in the OR employees because they are subjected to pollutants all the time. For that reason, the Benzo[a]pyrene concentration was quantified in specimens of blood obtained from 70 occupationally exposed people (Polluted Group) and 70 persons (Control Group). Additionally, they evaluated the effects of Benzo[a]pyrene on thyroid function (TF). The findings showed that PG people had considerably greater blood benzo[a]pyrene levels (P